2019
DOI: 10.1002/chem.201804632
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Treatment‐Assisted Molten‐Salt Strategy to Enhance Electrochemical Performances of Li‐Rich Assembled Microspheres by Tailoring Their Surface Features

Abstract: Constructing Li‐rich Mn‐based layered oxide (LMRO) assembled microspheres with fast kinetics and a stable surface will significantly improve discharge capacity and cyclic stability. In this work, a heat‐treatment‐assisted (HA) molten‐salt (MS) strategy has been designed to prepare LMRO assembled microspheres HA‐MS‐LMRO (LMRO with heat‐treatment‐assisted molten‐salt process). Electrochemical measurements demonstrate that HA‐MS‐LMRO possesses superior performance as a cathode for lithium‐ion batteries. It delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…The (108)/(110) and (006)/(102) doublets were obviously spitted, indicating that these cathodes had ordered structure. 16,17 Rietveld refinement was carried out based on the space group R 3 ¯m and chemical compositions determined from the ICP (Table I). The pre-calculated pattern matched well with the observed one.…”
Section: Resultsmentioning
confidence: 99%
“…The (108)/(110) and (006)/(102) doublets were obviously spitted, indicating that these cathodes had ordered structure. 16,17 Rietveld refinement was carried out based on the space group R 3 ¯m and chemical compositions determined from the ICP (Table I). The pre-calculated pattern matched well with the observed one.…”
Section: Resultsmentioning
confidence: 99%
“…Proses Leblanc ini didasarkan pada pemanggangan kerak garam (115)(116)(117)(118)(119)(120)(121)(122)(123)(124) dengan karbon dan gamping di dalam tanur putar dan sesudah itu dilakukan proses pengerasan hasilnya dengan air. Produk kasar dari reaksi ini dinamakan black ash (abu hitam).…”
Section: B Proses Leblancunclassified
“…Li et al. used heat treatment assisted molten salt strategy to improve the electrochemical performance of Li‐rich Mn‐based layered oxide (LMRO) assembled microspheres [45] . Previous results have shown that molten salt synthesis of spinel leads to controlled growth in size and shape of nano materials [46] .…”
Section: Introductionmentioning
confidence: 99%